Near surface characteristics of concrete containing supplementary cementing materials - Razak, H.A.; Chai, H.K.; Wong, H.S. (2004)
This paper presents the results of an investigation on the use of metakaolin and silica fume as supplementary cementing materials in enhancing the near surface properties of concrete. Metakaolin and silica fume mixtures, each with 10 replacement, were prepared and tested for initial surface absorption, water absorption and sorptivity. Metakaolin and silica fume were found to enhance the overall near surface characteristics of the concrete. The inclusion of metakaolin and silica fume greatly reduced the initial surface absorption, water absorption and sorptivity of concrete in varying magnitudes. Generally, the curing method adopted had significant effects on the near surface properties of concrete incorporating metakaolin or silica fume.